Genetic alterations and molecular mechanisms underlying hereditary intrahepatic cholestasis - Xie, Shuying; Wei, Shizhang; Ma, Xiao; Wang, Ruilin; He, Tingting; Zhang, Zhao; Yang, Ju; Wang, Jiawei; Chang, Lei; Jing, Manyi; Li, Haotian; Zhou, Xuelin; et al. (Frontiers in Pharmacology, 2023)
Hereditary cholestatic liver disease caused by a class of autosomal gene mutations results in jaundice, which involves the abnormality of the synthesis, secretion, and other disorders of bile acids metabolism. Due to the existence of a variety of gene mutations, the clinical manifestations of children are also diverse. There is no unified standard for diagnosis and single detection method, which seriously hinders the development of clinical treatment. Therefore, the mutated genes of hereditary intrahepatic cholestasis were systematically described in this review.